The Self Who Meets the Other: Deconstructing the “Well-Intentioned” Researcher Through an Ethic of Hospitality - Heringer, Rebeca (Alberta Journal of Educational Research, 2024)
The pursuit of anti-oppressive, cross-racial research has become ubiquitous in educational settings. Although some attention has been given to the complexities such an endeavor involves, more intricate and profound aspects that undergird such projects are revealed when examined through the lens of an ethic of hospitality. Based on a case-study focused on the experiences of Black refugee students in Manitoba, this article deconstructs the research journal that I kept throughout that project. Four overarching and intertwined themes are evidenced and discussed: the methodological decisions I had to make along the study, personal ambivalences experienced, feelings of powerlessness, and the (explicit) implications of my White identity. As such, the research journal here analyzed not only reveals the aporetic nature of hospitality but also several ethical complexities involved in the pursuit of hospitable, anti-oppressive research in a cross-racial setting, which have not received enough attention in current literature.